The emergence and development history of Demak Bintoro Kingdom - M Nur Rokhman; Lia Yuliana; Zulkarnain Zulkarnain (Universitas Negeri Yogyakarta, 2016)
This research is aimed to find the emergence and development of Demak kingdom. This research used the five stages historical research method according to Kuntowijoyo, which are topic selection, heuristic, verification, interpretation and writing. Kasultanan Demak is the first Islamic kasultanan in Java which was founded by Raden Patah in 1478. Demak area covers Jepara, Semarang, Tegal, Lembang, Jambi, islands among Kalimantan and Sumatera and some areas in Kalimantan islands. The glory era was in Sultan Trenggana administration who ruled from 1521-1546 M. After the death of Sultan Trenggana, there was power seizure in Demak Kingdom. This seizure occured between the Prince of Sekar Seda ing Lepen and Sunan Prawata who was the only son of Sultan Trenggana. Thus, there was murder conducted by Sunan Prawata towards the Prince of Sekar Seda ing Lepen. The son of Prince of Sekar Seda ing Lepen whose name was Arya Panangsang from Jipang avenged his father’s death by murdering Sunan Prawoto. One of dukes who fighted againts Arya Panangsang was Joko Tingkir. He was one of Sultan Trenggono’s son-in-law and ruled in Pajang. Reputedly, Joko Tingkir had purebred line of Majapahit that is Brawijaya V who was expelled by Girindrawardhana and subserved in Demak Kingdom. Keywords: maket, administration, and Islam Mataram